Fatigue in cancer patients in radiotherapy treatment (Research, Society and Development, 2022)
Cancer is the disease that kills the most people in the world, more than half of the cases per year go to their death, however there are several treatments in search of improvement and quality of life of cancer patients such as surgery, chemotherapy, radiotherapy, etc. All these treatments lead the patients to have fatigue, since they destroy both the good and the bad cells, and in most cases the good cells regenerate, the cancerous ones do not. Starting the side effects. Therefore, the aim of this paper is to describe fatigue in patients who undergo radiotherapy, and to explain which methods can alleviate it. The methodology used is a bibliographic and integrative review, with a qualitative approach and Bardin's method of analysis. Thus, the causes of fatigue stem from the treatment chosen and the tumor site. It is concluded that the best way to treat fatigue is by seeking alternatives to reduce it, among them the practice of daily physical exercises and abstaining from energy expenditure.